Study Of Maternal Death In Urban And Rural Based On Pregnancy Planning In East Sumba Regency 2014-2018 - Ngundju Awang, Mariana; Maria Kristin, Diyan; A.A. Woda, Wilhelmina (The Islamic Education and Multiculturalism Foundation, 2023)
Family Planning (Keluarga Berencana/KB) is closely related to reducing Maternal Mortality Rate (MMR). MMR is maternal death during pregnancy, childbirth and the puerperium. Reproductive behavior is a contributor to MMR in this case the 4Ts: too many pregnancies, too close distance, too young, and too old. The 2012 Demographic and Population Survey showed that around 32.5 percent of MMR occurred as a result of giving birth too old and too young, and around 34 percent due to too many pregnancies (more than 3 children). East Sumba Regency MMR in the last 5 years is quite high, number 1 or 2 is the highest in NTT Province after TTS. To determine the characteristics of maternal mortality in 2014 – 2018, pregnancy planning for mothers who died in East Sumba Regency and the relationship between maternal mortality and pregnancy planning in East Sumba Regency in 2014 – 2018. The type of research used is Analytical Descriptive Research with Cross-sectional Method. The population and sample are total maternal mortality from 2014 - 2018 which is 50 in urban and rural areas. Methods of collecting data using interviews using questionnaires to husbands/families of deceased mothers, Village Midwives and Coordinator Midwives regarding complete identity, age, education, occupation, parity, spacing of Acceptor card ownership, information obtained from the Midwife is detailed and systematic before choosing contraception. Most mothers have planned pregnancy but there is a tendency to follow the wishes of the client. Maternal mortality is not related to planning for pregnancy, but pregnant women who do not plan pregnancy well are at greater risk of death than mothers who plan to become pregnant conclusions and implications for nursing practice